Awareness of Corruption in the Community and Public Service: a Victorian Study. Issue 2 (23rd June 2014) - Graycar, Adam
Abstract : Corruption hurts the public and undermines government. This study of perceptions of corruption in Victoria shows that the community believes corruption is on the increase, yet this view is not shared by public servants. In general corruption is not on the radar of senior Victorian public servants. There are more perceptions of corruption in line agencies than in central agencies. Behaviours most commonly suspected and observed were hiring family and friends, conflict of interest, abuse of discretion and abuse of information. One‐ third of public servants surveyed thought there were opportunities for bribery, yet only 4% had suspected bribery and less than one per cent had personally observed it. Almost half do not believe they would be protected from victimisation should they report corruption. The data reported here poses challenges in thinking about corruption when devising integrity standards in the public service.